Effect of Home-based Pulmonary Rehabilitation on Fatigue in Patients with COPD - Zeinab Jokar; Farahnaz Mohammadi; Hamid Reza Khankeh; Saeid Fallah Tafti (Tehran University of Medical Sciences, 2012)
Background & Aim: Fatigue is a premature symptom in patients suffering from chronic obstructive pulmonary disease. This study aimed to determine effect of the home-based pulmonary rehabilitation on fatigue among patients with COPD. Methods & Materials: In this clinical trial, 36 patients were recruited among from 100 patients with COPD according to inclusion criteria in Masih Daneshvari hospital in 2010. Participants were allocated into two control and intervention groups using random block sampling. In the intervention group, the pulmonary rehabilitation program was implemented during three educational sessions in three consecutive days. Fatigue was measured using the Fatigue Severity Scale (FSS) before and seven weeks after discharge. Data were analyzed using descriptive and inferential statistical tests (Independent and paired t-test, chi-square and covariance analysis). Results: At baseline, the mean scores of fatigue were 47.11 and 47.50 in the experimental and control groups, respectively (P=0.902). After the intervention, the mean scores of fatigue reached 21.94 and 54.64 in the experimental and control groups, respectively (P<0.001). Conclusion: According to results of the study, home-based pulmonary rehabilitation nursing could decrease fatigue in patients with COPD.